(Re)presenting ‘order’ online - Bullock, Karen (Policing and society, 2018)
Embedded in Goffman's (1959) concept of impression management and drawing on interview data this article examines cultural and organisational features which come together to shape how police officers construct presentational strategies on social media. The article explores how in presenting an image institutions and individuals must give engaging expression which concurs to a dominant cultural script whilst, simultaneously, avoid giving off expressions which threaten individual and institutional efficacy, reputation and legitimacy. In so doing, it is argued that officers face, and must come to negotiate, a series of challenges. This article considers the nature of these challenges, the ways that institutions and individuals have responded to them and implications for the construction of ‘order’ online.